Tumor-targeted metabolic inhibitor prodrug labelled with cyanine dyes enhances immunoprevention of lung cancer - Wen Li; Jiali Huang; Chen Shen; Weiye Jiang; Xi Yang; Jingxuan Huang; Yueqing Gu; Zhiyu Li; Yi Ma; Jinlei Bian (Elsevier, 2024)
Recent progress in targeted metabolic therapy of cancer has been limited by the considerable toxicity associated with such drugs. To address this challenge, we developed a smart theranostic prodrug system that combines a fluorophore and an anticancer drug, specifically 6-diazo-5-oxo-l-norleucine (DON), using a thioketal linkage (TK). This system enables imaging, chemotherapy, photodynamic therapy, and on-demand drug release upon radiation exposure. The optimized prodrug, DON-TK-BM3, incorporating cyanine dyes as the fluorophore, displayed potent reactive oxygen species release and efficient tumor cell killing. Unlike the parent drug DON, DON-TK-BM3 exhibited no toxicity toward normal cells. Moreover, DON-TK-BM3 demonstrated high tumor accumulation and reduced side effects, including gastrointestinal toxicity, in mice. This study provides a practical strategy for designing prodrugs of metabolic inhibitors with significant toxicity stemming from their lack of tissue selectivity.